Logística da distribuição de materiais em pavimentação rodoviária : uma modelagem em programação matemática - Lima, Roberto Xavier de (2003)
The objective of this paper is to produce a mathematical model which relates the geometric and geotechnical features of a road with the allocation of materials, searching for a minimum execution cost. It is proposed a linear programming model to optimize the earthworks and paving services. Itwill be possible, with this model, to analyze cases of different soil strata and different degrees ofcompaction. The borrow pit materials are allocated in the most economical way and itis possible to incorporate more details, like mixture of materials , for instance. The software LINGO was used to solve the model and EXCEL was used as interface for data input. The proposed model demonstrated possible cost savings in earthwork allocations, so it is expected that earthwork and paving optimization with linear programming reduce considerably the road construction costs.